ANALISIS POTENSI LIKUIFAKSI BERDASARKAN DATA SPT MENGGUNAKAN METODE HYPERBOLIC FUNCTION DENGAN VARIASI MAGNITUDO - Andini Chaerania; Dian Purnamawati Solin; Himatul Farichah (LPPM Universitas Abdurrab, 2025)
Liquefaction occurs when solid soil transforms into a liquid state, causing a loss of strength. Yogyakarta is one of the areas prone to liquefaction. The 6.2 magnitude earthquake that struck Yogyakarta in 2006 triggered liquefaction in Bantul and Sleman regencies. Therefore, in analyzing liquefaction potential, variations in earthquake magnitudes of 4, 5, 6, and 7 are considered. This study employs the Hyperbolic Function method, with the research point located at a single site, BH-93. A low N-SPT value has the potential to cause liquefaction, and if subjected to an earthquake with a magnitude greater than 5, it may undergo deep liquefaction.